An acoustic survey of baleen whales off Great Barrier Island, New Zealand - M. A. McDonald (New Zealand Journal of Marine and Freshwater Research, 2006)
Acoustic recordings of baleen whale calls were analysed for the calendar year 1997 from a pair of fixed hydrophones located 5 km east of Great Barrier Island, New Zealand. The primary goal of the study was to examine blue whale seasonally and song type as part of a larger worldwide study. Calls were recorded from blue whales of two song types, fin whales, humpback whales, Bryde's whales, and of two unknown call types, each probably produced by Bryde's whales. The peak of calling density was May through September for the blue, fin, and humpback whales. The known Bryde's whale calls occurred year‐round and the probable Bryde's whale calls occurred from May through December. Blue whale songs of a type so far known only from New Zealand waters were detected within 2 km of shore and occurred four times from June to December, whereas the Southern Ocean blue whale songs were detected only further offshore in mid‐winter. Bryde's whale calls were the most abundant type and often occurred near the hydrophones. These data provide a baseline from which future recordings from the same hydrophones could be compared.